Impact of soil application with humic acid and foliar spray of milagro bio-stimulant on vegetative growth and mineral nutrient uptake of Nonpareil almond young trees under Nubaria conditions - Abourayya, Mahmoud Sami (2021)
The results showed that different treatments improved the vegetative growth of seedlings, stem length, diameter, number of branches and leaves, leaf area, leaf fresh and dry weight, and specific leaf dry weight as well as leaf chlorophylls and minerals content comparing with untreated young trees. Soil application of 30 g humic acid along with 30 ml/l milagro per young tree as foliar spray was the promising treatment as a new fertilization technique that is non-chemical, low-cost, and environmentally safe for improving growth and nutritional status of Nonpareil almond young trees under Nubaria conditions.